Coronavirus Receptor Expression Profiles in Human Mast Cells, Basophils, and Eosinophils - Lina Degenfeld-Schonburg; Irina Sadovnik; Dubravka Smiljkovic; Barbara Peter; Gabriele Stefanzl; Clemens Gstoettner; Peter Jaksch; Konrad Hoetzenecker; Clemens Aigner; Christine Radtke; Michel Arock; Wolfgang R. Sperr; et al. (Cells, 2024)
A major problem in SARS-CoV-2-infected patients is the massive tissue inflammation in certain target organs, including the lungs. Mast cells (MC), basophils (BA), and eosinophils (EO) are key effector cells in inflammatory processes. These cells have recently been implicated in the pathogenesis of SARS-CoV-2 infections. We explored coronavirus receptor (CoV-R) expression profiles in primary human MC, BA, and EO, and in related cell lines (HMC-1, ROSA, MCPV-1, KU812, and EOL-1). As determined using flow cytometry, primary MC, BA, and EO, and their corresponding cell lines, displayed the CoV-R CD13 and CD147. Primary skin MC and BA, as well as EOL-1 cells, also displayed CD26, whereas primary EO and the MC and BA cell lines failed to express CD26. As assessed using qPCR, most cell lines expressed transcripts for CD13, CD147, and ABL2, whereas ACE2 mRNA was not detectable, and CD26 mRNA was only identified in EOL-1 cells. We also screened for drug effects on CoV-R expression. However, dexamethasone, vitamin D, and hydroxychloroquine did not exert substantial effects on the expression of CD13, CD26, or CD147 in the cells. Together, MC, BA, and EO express distinct CoV-R profiles. Whether these receptors mediate virus–cell interactions and thereby virus-induced inflammation remains unknown at present.